Tablet-based disclosure counselling for HIV-infected children, adolescents, and their caregivers: a pilot study. Issue 3 (28th September 2018) - McHenry, Megan S; Apondi, Edith; McAteer, Carole I; Nyandiko, Winstone M; Fischer, Lydia J; Ombitsa, Ananda R; Aluoch, Josephine; Scanlon, Michael L; Vreeman, Rachel C
Abstract : Background: Overwhelmed, under-trained medical staff working in resource-limited settings need efficient resources for HIV disclosure counselling. The objective of this study was to describe providers' experiences using tablet computers for disclosure-related counselling with HIV-infected children and their caregivers in western Kenya, with additional perspectives from adolescents. Methods: A qualitative study design was implemented at three HIV clinics in western Kenya (Bumala, Busia and Port Victoria) within the Academic Model Providing Access to Healthcare (AMPATH) partnership. Twenty-one healthcare providers involved with paediatric disclosure were recruited and enrolled in the study. Initial interviews focused on understanding current disclosure practices and barriers. Tablets containing disclosure-related resources were distributed. Resources included short narrative videos created in this context to highlight issues relevant to child HIV disclosure. Results: Providers reported tablets improved disclosure, child participation, and medication adherence. All reported that reviewing materials increased their knowledge and comfort with disclosure. The most frequently used materials were the narrative videos and an animated video explaining the importance of medication adherence. Time was a major barrier for using the tablet. Clinician self-education persisted at one-year follow-up. Adolescents expressed enjoyment from viewing the tablet resources and had a better understanding of the importance of medication adherence. Conclusions: Tablet computers containing resources for disclosure are an acceptable and potentially effective resource to help providers support families with disclosure. Further work is needed to train the clinical providers in using the resources in a developmentally appropriate manner, and to develop new resources on adolescent-specific and HIV-related topics.